Ras and Rab Interactor 3: From Cellular Mechanisms to Human Diseases - Shen, Ruinan; Murphy, Caitlin J; Xu, Xiaowen; Hu, Mingzheng; Ding, Jianqing; Wu, Chengbiao (Frontiers in Cell and Developmental Biology, 2022)
The Ras and Rab interactor 3 (RIN3) is a guanine nucleotide Exchange Factor (GEF) that acts on members of the Rab5 small GTPase family to regulate cellular trafficking and function. Through stimulating the activation of Rab5, RIN3 plays an important role in the early stages of endocytosis. In addition, RIN3 activates Ras, another small GTPase, to participate in multiple cell-signaling pathways. Increasing evidence has pointed to that dysregulation of RIN3 activity may contribute to the pathogenesis of several disease conditions in human such as Paget’s Disease of the Bone (PDB), chronic pulmonary obstructive disease (COPD) and obesity, for which a significant number of variants have been identified by recent genome-wide association studies (GWAS). Interestingly, all disease associated missense mutations identified thus far are located on the functional domains of the RIN3 protein, while most variants are found on the noncoding regions of RIN3 gene, likely to be promotors or enhancers. Most interestingly, recent emerging evidence has linked RIN3 to Alzheimer’s disease (AD). However, neither the protein structure nor the exact function of RIN3 (except for its GEF activity) have been fully elucidated, making it difficult to decipher how these missense mutations/variants contribute to disease pathogenesis. Nevertheless, we attempt to review current literatures to better understand the physiological function of RIN3. We are particularly intrigued by emerging evidence suggesting that increased expression of RIN3 likely contributes to early cellular pathogenesis of AD, and we provide testable hypothesis regarding the potential disease mechanism(s).